(untitled) (Journal of Parents and Teachers, 2014)
Before selecting an educational method, we must first take a critical look at the current system, since for many years this teaching has been governed by the stereotypes of a sexist society. Despite the introduction of the (LOGSE) in 1970, which sought to alleviate this discrimination, we still observe great differences despite the coexistence of both sexes within the classroom. Coeducation tries to break the cannon that have not allowed both sexes to be equal, much of the blame for this sexist mentality lies with the media, due to a misunderstanding of the areas in which an individual may or may not fit into an egalitarian society. In short, this variant tries to eliminate the dominant roles implicit in men, allowing women to shed their role as latent helpers even in our society.